Diagnostics of transport potential of freightage systems - Горяинов, Алексей Николаевич; Литовченко, Е.С. (Eastern-European Journal of Enterprise Technologies, 2010)
The problems of diagnostic in freightage systems are considered. Allocated a place of diagnostic methods in the decision support system. An integrated index of the principles of transport quality work is proposed and the models describing the individual principles are submitted.